A case report and review of literature of Dieulafoy's disease of bronchus: A rare life-threatening pathologic vascular condition. Issue 7 (February 2019) - Zhou, Pengcheng; Yu, Wei; Chen, Kelin; Li, Xuelian; Xia, Qianming
Abstract: Rationale: Dieulafoy's lesions are characterized by the presence of a dysplastic artery in the submucosa, most frequently associated with gastrointestinal hemorrhage. They are rarely identified in the bronchial submucosa and can cause massive or fatal hemoptysis Patient concerns: The patient was a 62-year-old male farmer with intermittent hemoptysis of approximately 2 years duration and a definite diagnosis could not be established. Diagnosis: A thorax-computed tomography at our hospital revealed that the bronchus of left lower lobe was narrowed with associated local atelectasis, and lung cancer was suspected. A bronchoscopy showed a slit-like stenosis of the left lower lobe, swollen and smooth mucosa, and a significantly wider subsection carina. Interventions: A fatal hemorrhage occurred during biopsy and, rescue and resuscitation measures were immediately taken. A double-lumen endotracheal intubation was implanted and single-lung ventilation was started to maintain oxygenation. Hemoptysis completely stopped after bronchial artery embolization. Outcomes: The patient eventually died of disseminative intravascular coagulation and multiple organ failure. Bronchial arteriography and subsequent autopsy confirmed Dieulafoy's disease of the bronchus. Lessons: In cases with recurrent unexplained hemoptysis, where CT chest or thoracic radiography show no abnormalities, pulmonologist should suspect a bronchial Dieulafoy's disease and avoid blindly performing bronchoscopy guided biopsy, which may result in fatal hemoptysis.